Evolution of long distance students' mobility: The role of the air transport service in Italy - Mattia Cattaneo; Paolo Malighetti; Stefano Paleari; Renato Redondi (European Regional Science Association (ERSA), 2015)
Introduction There is a large consensus that the amount of human capital in areas plays a crucial role for regional economic development. Previous evidence on regional economics highlight that a higher concentration of human capital is associated with more population, employment growth, income and ability to innovate (e.g., Carlino et al., 2007; Glaeser and Saiz, 2004; Glaeser, 2005). Therefore, it is crucial to identify the factors that drives differences in human capital accumulation in specific areas (e.g., Boschma at al., 2013). Among others, universities have been identified as focal institutions for the attraction of highly skilled human capital toward specific areas, being firstly responsible for the attractiveness to students from different areas. Although some recent contributions have already investigated whether universities are able to affect the distribution of human capital at a regional level (Ciriaci, 2013; Abel and Deitz, 2012), less attention has been paid to the effects that the evolution of transport infrastructures play in this respect. Due to the growth of interest in the concept and the few attempts to deal with this topic, this paper aims to investigate how the Italian higher education system and transport infrastructures co-evolve over time, mainly focusing on the impact of transports infrastructures? changes on the long distance mobility of students. In the last decade, students aiming to increase their opportunities in the labour market and enhance their social status have become more prone to move, relocating in wealthier areas, whereas, at the same time, long distance students? mobility has been facilitated by the decrease of travel costs (e.g. Ryanair, Freccia Rossa). Data and Methodology Relying on the population of 75 private and public universities in Italy over the period 2002-2012 and the changes that affected both the air transportation and the high-speed rail system we investigate the long distance mobility of first-time first-year university students (more than 300 km from their households) departing from each Italian province. Consistently with the literature on spatial interaction analyses, we investigate the effects of transport infrastructures rely on a competition destinations model (e.g., Sà et al. 2004, Cattaneo et al. 2014). Results Preliminary results suggest that long distance students? mobility has been affected by the evolution of transport infrastructures with an important impact of low cost airlines from Southern to Northern Italian regions. The change in the distribution of Italian students that has been occurred in the last years (Cattaneo et al. 2014; Long 2013) is found to be facilitated by the presence of more developed transport infrastructures, which have decreased the costs associated to long distance mobility.
Keywords: L9; O1; I2; 330; University students; transport infrastructures; attractiveness to students